Determinants of reproductive health behavior among adolescents: A cross-sectional study - Putu Noviana Sagitarini; Ni Komang Tri Agustini; Ida Ayu Ningrat Pangruating Diyu; Ni Made Candra Citra Sari (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Adolescents are vulnerable to reproductive health problems due to limited knowledge, inadequate access to information, and a lack of family support. These conditions may influence adolescents’ reproductive health maintenance behaviors and increase the risk of reproductive health problems in the future. Research Methodology: This study aimed to analyze the factors influencing adolescent reproductive health behavior. This study employed a quantitative analytic design with a cross-sectional approach conducted among 243 female students at SMPN 1 Kediri Tabanan. Data were collected using a structured questionnaire that included variables of knowledge, attitudes, peer influence, access to information, family support, and reproductive health behavior. Data analysis was performed using the Spearman Rho test and ordinal logistic regression. Result: The results showed that knowledge, attitudes, access to information, and family support were significantly associated with adolescent reproductive health behavior (p < 0.05), whereas peer influence was not significant. Multivariate analysis indicated that knowledge and family support simultaneously had a significant effect on adolescent reproductive health behavior, with family support emerging as the dominant factor (OR = 2.64). Conclusion: Adolescent reproductive health behavior is influenced by both individual and environmental factors. Therefore, integrated interventions that enhance health education and strengthen family involvement are necessary to promote optimal reproductive health behaviors among adolescents.